Analysis of Agra Mas Bus Service Level Case Study of PGC East Jakarta Route – Soekarno Hatta International Airport - Dermawan, Widodo Budi; Setiawan, Bambang Adi (Journal of World Conference (JWC), 2020)
The method used in this study is the Importance Performance Analysis (IPA) method. This research was conducted to determine passenger satisfaction, evaluate service levels by referring to service standard indicators from the Directorate General of Land Transportation. The results of the Bus Operational Performance analysis results refer to the Directorate General of Land Transportation standards, the overall results of operational performance have been included in the Good category with a value of 24 points. the results of the questionnaire stated that the service performance was very good (SB) by 16%; Good (B) of 52%; Fairly Good (CB) of 25%; Poor (KB) by 6% and Not Good (TB) by 0%, regarding the 5 Likert scale. From the Cartesian diagram there are several aspects of concern regarding the level of service, quadrant I there are 8 attributes that are considered important by consumers and their service is very satisfying, Quadrant II there are 1 attributes that are considered very important by customers but the service is not satisfactory.